2021
DOI: 10.1093/bib/bbab262
|View full text |Cite
|
Sign up to set email alerts
|

Discovering common pathogenetic processes between COVID-19 and diabetes mellitus by differential gene expression pattern analysis

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the newly discovered coronavirus, SARS-CoV-2. Increased severity of COVID-19 has been observed in patients with diabetes mellitus (DM). This study aimed to identify common transcriptional signatures, regulators and pathways between COVID-19 and DM. We have integrated human whole-genome transcriptomic datasets from COVID-19 and DM, followed by functional assessment with gene ontology (GO) and pathway analyses. In peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…28,29 Rahman et al have shown that hyperglycemia and COVID-19 have a synergistic inflammatory effect that could be due to a common differential gene expression pattern between COVID-19 and diabetes, suggesting the involvement of biological processes and pathways commonly dysregulated. 30 In addition to diabetes, we have found that higher BMI was also significantly associated with higher odds of having more severe forms of COVID-19. These results suggest an association of metabolic comorbidities with adverse outcomes of COVID-19.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…28,29 Rahman et al have shown that hyperglycemia and COVID-19 have a synergistic inflammatory effect that could be due to a common differential gene expression pattern between COVID-19 and diabetes, suggesting the involvement of biological processes and pathways commonly dysregulated. 30 In addition to diabetes, we have found that higher BMI was also significantly associated with higher odds of having more severe forms of COVID-19. These results suggest an association of metabolic comorbidities with adverse outcomes of COVID-19.…”
Section: Discussionmentioning
confidence: 65%
“… 28 , 29 Rahman et al have shown that hyperglycemia and COVID‐19 have a synergistic inflammatory effect that could be due to a common differential gene expression pattern between COVID‐19 and diabetes, suggesting the involvement of biological processes and pathways commonly dysregulated. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One COVID-19 dataset (GEO accession ID: GSE171110) consisted of 44 COVID-19-infected whole-blood samples and 10 healthy whole-blood samples with Illumina HiSeq 2000 ( 22 ). Another COVID-19 dataset (GEO accession ID: GSE152418) contained 16 peripheral blood mononuclear cells samples and 17 healthy samples ( 23 ). Similarly, the HIV dataset (GEO accession ID: GSE37250) consisted of 274 positive HIV-infected whole-blood samples, 263 negative HIV-infected whole-blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, all the aforementioned pieces of evidence create an urgent need that the possible crosstalk between SARS-CoV-2 and neurodegenerative disorders such as PD should be taken into consideration. Other studies have been carried out assessing other potential comorbidities in respect to COVID-19 including chronic kidney disease (Auwul et al 2021) and diabetes mellitus (Rahman et al 2021).…”
Section: Introductionmentioning
confidence: 99%